CREANUIS: a non-linear radiofrequency ultrasound image simulator - Varray, François; Basset, Olivier; Tortoli, Piero; Cachard, Christian (Ultrasound in medicine & biology, 2013)
Nonlinear ultrasound methods are widely used in clinical applications for tissue or contrast harmonic imaging. Accurate non-linear imaging simulation tools are required in research studies for the development of new methods. However, in existing simulators, the possible inhomogeneity of the coefficient of non-linearity, which is generally observed in tissue and in particular when contrast agents are involved, has not yet been implemented. This article describes a new ultrasound simulator, called CREANUIS, devoted to the computation of B-mode images where both linear and non-linear propagation in media is considered, with a possible inhomogeneous coefficient of non-linearity. The resulting fundamental images, based on a spatially variant and non-linear point spread function, are in accordance with those obtained through the reference linear FieldII simulator, with computation time reduced by a factor of at least 1.8. Non-linear images of media exhibiting inhomogeneous coefficients of non-linearity are also provided. The simulation software can be freely downloaded from our website.